Francois Hollande's Idiosyncratic Factors In French Isis Policy - Ilham Rizki Febriansyah (Jurnal Indonesia Sosial Teknologi, 2023)
The leadership style of Francois Hollande it was means a lot to the government of France. It is all about Hollande’s personality who is a very intuitive look threat against ISIS in France. Whose decision-making process by Francois Hollande has made France more aggressive than before. The researcher would explain how idiosyncratic factors of Francois Hollande’s policy against ISIS in France. The purpose of the research is to know how individual psychological can influence the decision-making process and behavior of nations. Data was collected by literature study and online website research. The result of the research tries to describe how the idiosyncrasy of Francois Hollande is very fluently to France’s policy against ISIS, which France’s response would make a positive impact and negative impact internal or external. Francois Hollande is an obsessive-compulsive type leadership.